La successione tardo triassica del Gebel di Garian (Libia) : esemplificazione del principio di Walther - Assereto, Riccardo (Rivista italiana di paleontologia e stratigrafia, 1970)
Keywords: Géologie -- Djebel Nefousa

Middle, Upper Jurassic and Lower Cretaceous sedimentary environments of the Djebel Nefusa region, northwestern Libya - Hodgkinson, Richard J.; Walley, Christopher D. (Annual report - Society for Libyan Studies, 1977)
Carbonate and clastic sediments of Jurassic and Cretaceous age are exposed along the fault-scarp of Djebel Nefusa in north-western Libya. Previous geological investigations have been mainly restricted to the eastern sector of the scarp. Recent studies by the authors in the western sector of Djebel Nefusa and on equivalent sediments in southern Tunisia have allowed the first regional interpretation of these rocks. The area studied lies geographically and geologically at the edge of the Saharan Platform, a large cratonic block, composed of rocks of Precambrian-Palaeozoic age. To the north and east lies a downfaulted sedimentary basin (Gabes-Sabratha Basin) containing a large thickness of Mesozoic sediments. The location of the sections measured along Djebel Nefusa are depicted in Fig.1. The stratigraphic nomenclature of the rock succession of Djebel Nefusa was first established in the east and continued laterally towards the west by later workers. Difficulties in the application of this nomenclature are presented by the recognition of facies changes previously overlooked by earlier investigators. However, as a framework for understanding these changes and the sedimentary processes which caused them, the stratigraphy erected by Magnier (1963) is adopted.
Keywords: Géologie -- Djebel Nefousa

Geophysical Studies of North African Cenozoic Volcanic Areas: III. Garian, Libya - Ade-Hall, J. M.; Gerstein, Susann; Gerstein, Robert E.; Reynolds, Peter H.; Dagley, P.; Mussett, A. E.; Hubbard, T. P. (Canadian Journal of Earth Sciences, 1975)
Paleomagnetic and K/Ar whole rock absolute age data are described for material from the Garian area of Libya, centered at 13°E, 32°N. Within-unit cleaned paleomagnetic directions from the essentially unaltered lavas are very well defined and can almost certainly be taken as reliable measurements of the geomagnetic field direction during the initial cooling of each flow. However, the distributions of mean direction, from which the effect of repeated sampling of the field at one time has been removed, does not suggest that a reversing axial dipole field has been recorded in a representative manner. Both N and R groups of directions are azimuthally elongated, and the average poles for the N and R groups differ by 21°, or four times the 95% level uncertainty for each average pole. A number of possible physical explanations for the paleomagnetic results are discussed. The conventional overall average pole at 88°N, 123°E, δp: 3°, δm: 7 °does not differ significantly from the geographic pole, a result which agrees closely with that of Schult and Soffel (1973). However, the value of these overall average poles in estimating absolute plate motion must await an understanding of the sources of the asymmetries in the paleomagnetic data.
Keywords: Géologie -- Djebel Nefousa

Large-scale landslides in north-western Libya - Ostaficzuk, Stanislaw (Acta Geologica Polonica, 1973)
Keywords: Géologie -- Djebel Nefousa